Zur Kenntnis der Gattung Evagetes Lepeletier, 1845 (Hymenoptera: Pompilidae). - Wolf, Heinrich (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The publication gives a survey and a key of the species and subspecies, known so far, of the parasitic genus Evagetes Lepeletier (Hymenoptera, Pompilidae), diagnoses of the genus and the subgenera, two of which are new, diagnose of 21 new species and subspecies in the keys, and illustrations of the male anal sternites and the copulation organs of all known species.Nomenclatural Actsalmoravidus Wolf, 1970 (Evagetes), spec. n.atatuerki Wolf, 1970 (Evagetes), spec. n.barbarescus Wolf, 1970 (Evagetes), spec. n.Carinevagetes Wolf, 1970 (Evagetes), sgen. n.Contemptevagetes Wolf, 1970 (Evagetes), sgen. n.fortunatus Wolf, 1970 (Evagetes), spec. n.iconionus Wolf, 1970 (Evagetes), spec. n.invreai Wolf, 1970 (Evagetes), spec. n.juncoi Wolf, 1970 (Evagetes), spec. n.linsenmaieri Wolf, 1970 (Evagetes), spec. n.mongolicus Wolf, 1970 (Evagetes), spec. n.nasobema Wolf, 1970 (Evagetes), spec. n.ophirus Wolf, 1970 (Evagetes), spec. n.paulinus Wolf, 1970 (Evagetes), spec. n.pseudoleucopterus Wolf, 1970 (Evagetes), spec. n.tingitanus Wolf, 1970 (Evagetes), spec. n.tumidinus Wolf, 1970 (Evagetes), spec. n.lixinus Wolf, 1970 (Evagetes barbarescus), sspec. n.aterrimus Wolf, 1970 (Evagetes contemptus), sspec. n.obscurodubius Wolf, 1970 (Evagetes dubius), sspec. n.infernalis Wolf, 1970 (Evagetes magrettii), sspec. n.lusitanicus Wolf, 1970 (Evagetes pectinipes), sspec. n.mediterraneus Wolf, 1970 (Evagetes pectinipes), sspec. n.minotaurus Wolf, 1970 (Evagetes pectinipes), sspec. n.mavromoustakisi Wolf, 1970 (Evagetes pontomoravicus), sspec. n.Pseudevagetus Wolf, 1970 (Pompilidae), gen. n.ichnusus Wolf, 1970 (Pseudevagetes), spec. n.